Anisotropic behaviour of AZ31B sheet at high strain rates - Ahmad, Iram Raza (2013)
The anisotropic effects on the mechanical response of AZ31B sheet at high strain rates have been analyzed. The experimental results indicate that the stress-strain behaviour of the alloy is highly anisotropic and rate sensitive. However, anisotropy of the mechanical properties of the alloy is less significant at higher strain rates. Under tensile loading, the anisotropic behaviour of the alloy is less significant as compare to its behaviour under compression. In both compression and tensile loading the alloy shows significant rate sensitivity as compare to quasi-static strain rates but at higher rates it is less significant. The maximum stress is observed to reach nearly 600 MPa for transverse direction impact. The tension-compression asymmetry is observed in the alloy.